TRPV1 Channel Contributes to the Behavioral Hypersensitivity in a Rat Model of Complex Regional Pain Syndrome Type 1 - Hu, Qimiao; Wang, Qiong; Wang, Chuan; Tai, Yan; Liu, Boyu; Shao, Xiaomei; Fang, Jianqiao; Liu, Boyi (Frontiers in Pharmacology, 2019)
Complex regional pain syndrome type 1 (CRPS-I) is a debilitating pain condition that significantly affects life quality of patients. It remains a clinically challenging condition and the mechanisms of CRPS-I have not been fully elucidated. Here, we investigated the involvement of TRPV1, a nonselective cation channel important for integrating various painful stimuli, in an animal model of CRPS-I. A rat model of chronic post-ischemia pain (CPIP) was established to mimic CRPS-I. TRPV1 expression was significantly increased in hind paw tissue and small to medium-sized dorsal root ganglion (DRG) neurons of CPIP rats. CPIP rats showed increased TRPV1 current density and capsaicin responding rate in small-sized nociceptive DRG neurons. Local pharmacological blockage of TRPV1 with the specific antagonist AMG9810, at a dosage that does not produce hyperthermia or affect thermal perception or locomotor activity, effectively attenuated thermal and mechanical hypersensitivity in bilateral hind paws of CPIP rats and reduced the hyperexcitability of DRG neurons induced by CPIP. CPIP rats showed bilateral spinal astrocyte and microglia activations, which were significantly attenuated by AMG9810 treatment. These findings identified an important role of TRPV1 in mediating thermal and mechanical hypersensitivity in a CRPS-I animal model and further suggest local pharmacological blocking TRPV1 may represent an effective approach to ameliorate CRPS-I.